Analysis of Environmental Practices in Innovations of Products and Processes - Theis, Vanessa; Schreiber, Dusan (Sustainability in Debate, 2015)
The objective of this paper is to identify how environmental practices are embedded in product innovation activities and processes in the metal-mechanic sector companies located in the region of the Rio dos Sinos Valley, Rio Grande do Sul, Brazil. The state hosts around 9.800 establishments in this sector, with prevailing micro and small enterprises. Using the authors’ contact network, a multiple case study was conducted in five organizations, adopting the criteria of the actors’ accessibility and avaibility. Data were collected through in-depth interviews, which were transcribed and analysed through content analysis. Results showed that companies are working to meet the legal requirements and that the difference in environmental issues occurs only in industrial processes. Thus, it appears that organizations are working to insert the environmental practices only in innovation processes.